Fire Resistance of Geopolymer Materials—A Change in Physical and Mechanical Properties - Tarreck Mahaman Manssour Issa; Katarzyna Mróz; Mateusz Sitarz; Izabela Hager; Ewa Słupska (Materials Proceedings, 2023)
Geopolymers are new environmentally friendly cementitious materials that may offer an alternative to Ordinary Portland Cement. Not only do they have excellent mechanical properties, but they also have high temperature resistance. This research focuses on the high temperature exposure effect on geopolymer mortars. Two types of geopolymer mortars were prepared and exposed to different temperatures (20, 200, 400, 800 °C). The main goal of this work is to assess the changes in the mechanical and physical properties of geopolymer mortars after being exposed to a high temperature. Two types of mixtures were tested: one containing 100% fly ash (M0-K) and the other one containing 50% fly ash and ground Granulated blast furnace slag (M50-K). The paper presents an evaluation of compressive and tensile strength, density, porosity, and ultrasonic pulse velocity for both M50-K and M0-K after exposure to high temperatures.